Popis stanja gozdov v Sloveniji leta 1998 na 16x16 km mreži, spremembe stanja v obdobju 1987-1998 in stanje gozdov v Evropi - Mavsar, Robert (Zbornik gozdarstva in lesarstva, 1999)
The article presents the results of the 1998 forest condition survey which wascarried out on the 16 x 16 km grid. The survey comprised 1008 trees on 43 plots. The average defoliation was 23.5% and 29% of the sample trees were damaged (trees with a defoliation rate higher than 25%. The situation in otherEuropean countries is similar to the situation in Slovenia - a slight increase has been detected in the average defoliation. In the article the datafor some countries are presented. In the survey we included damages with identifiable causes. The results are similar to those in 1997. We found identifiable damages on 41% of the sample trees, the main damage being in the crown (insects) and on the trunk (cutting and skidding).
Keywords: environmental protection; forestry; gozdarstvo; propadanje gozdov; raziskave; Slovenia; Slovenija; varstvo okolja